THE IMPLEMENTATION OF TPS (THINK, PAIR, SHARE) LEARNING MODEL BY USING CUE CARD MEDIA ON TEACHING AND LEARNING WRITING FOR THE ELEVENTH YEAR STUDENTS OF SMA N 1 KARANGNONGKO IN ACADEMIC YEAR OF 2023/2024 - Ariyani, Linda Ajeng; Haryanti, Sri; Widayanti, Sukasih Ratna (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2024)
Abstract The aim of this study is to answer the question which becomes the problem of this study “How is the implementation of TPS (Think, Pair, Share) learning model by using cue card media on teaching and learning writing for the eleventh year students of SMA N 1 Karangnongko in academic year of 2023/2024?”. This study is qualitative research. The data in this study are the result of observation in the form of field note, the result of teacher and student’s interview, and the field note data that contained the process from the implementation of TPS (Think, Pair, Share) learning model by using cue card media. The sources of data are the English teacher and the students. The data were collected through observation, interview, and documentation. The writer used three concurrent flows of activities to analyze the data, namely data reduction, data display, and conclusion drawing/verification. After analyzing the data, the writer found aspects of implementing TPS (Think, Pair, Share) by using cue card media on teaching and learning writing. Firstly, the learning material is narrative text. Secondly, the learning steps are done by the teacher in carrying out the learning activities by implementing TPS (Think, Pair, Share) learning model by using cue card media. The learning steps consist of opening, main activity, and closing. The result of implementing Think, Pair, Share learning model by using cue card media shows that the teacher and the students are very excited and enthusiastic in using the combination of this learning model and learning media. Keywords: cue card; implementation; think; pair; share; writing becomes the problem of this study “How is the implementation of TPS (Think, Pair, Share) learning model by using cue card media on teaching and learning writing for the eleventh year students of SMA N 1 Karangnongko in academic year of 2023/2024?”. This study is qualitative research. The data in this study are the result of observation in the form of field note, the result of teacher and student’s interview, and the field note data that contained the process from the implementation of TPS (Think, Pair, Share) learning model by using cue card media. The sources of data are the English teacher and the students. The data were collected through observation, interview, and documentation. The writer used three concurrent flows of activities to analyze the data, namely data reduction, data display, and conclusion drawing/verification. After analyzing the data, the writer found aspects of implementing TPS (Think, Pair, Share) by using cue card media on teaching and learning writing. Firstly, the learning material is narrative text. Secondly, the learning steps are done by the teacher in carrying out the learning activities by implementing TPS (Think, Pair, Share) learning model by using cue card media. The learning steps consist of opening, main activity, and closing. The result of implementing Think, Pair, Share learning model by using cue card media shows that the teacher and the students are very excited and enthusiastic in using the combination of this learning model and learning media. Keywords: cue card; implementation; think; pair; share; writing